Sanksi Pidana Bagi Pelaku Penimbun Masker Selama Masa Pandemi Covid-19 - Kadek Wahyu Juniarta; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
Hoarding is an activity of collecting goods so that they become scarce in the market and are sold at high prices. During the COVID-19 pandemic, people really need masks, but people who don't have empathy for their fellow citizens hoard masks so that they become scarce and the price becomes expensive. The purpose of this study is to reveal the legal arrangements against the perpetrators of hoarding masks during the COVID-19 pandemic and criminal sanctions against those who hoard masks during the COVID-19 pandemic. In this study using a statutory approach and a conceptual approach. Sources of legal materials applied are primary legal materials and secondary legal materials. the technique in collecting legal materials used is a literature study technique which is then analyzed systematically. The results of the study indicate that criminal sanctions against perpetrators of hoarding masks are based on Article 107 of Law Number 7 of 2014 with a maximum imprisonment of 5 years or a maximum fine of Rp. 50,000,000,000.00. In Law Number 5 of 1999 sanctions can also be imposed, in the form of administrative sanctions, basic criminal sanctions, additional criminal sanctions. The government must be able to provide appropriate sanctions for the perpetrators of hoarding masks because they have violated and threatened the interests of the community.